PENGUATAN PENDIDIKAN DAYAH DI ERA DIGITAL - Nazaruddin, Nazaruddin; Yani, Ahmad; Chalirafi, Chalirafi; Khaira, Alfi; Syamsuddin, Syamsuddin (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Agama Islam Jamiatut Tarbiyah Lhoksukon, 2024)
This study aims to analyze the implementation of digitalization at Dayah Darul Muarif and its impact on the quality of education. The digitalization at this dayah includes the use of educational software, online learning, and the integration of information technology in teaching and administrative management. The results of the study show that digitalization brings various positive impacts, such as increased access to information, more interactive learning, and management efficiency. However, the implementation of digitalization also faces several challenges, including infrastructure limitations, human resource readiness, and high implementation costs. With continuous support from various parties and appropriate strategies, this dayah can continue to optimize digital technology to improve the quality of its education. This study provides important insights for other traditional educational institutions that wish to adopt digital technology in their education systems.